CSIG-06. THE MOLECULAR SUBTYPE OF PRIMARY GLIOBLASTOMA CELLS CORRELATES WITH RESPONSE TO THERAPEUTIC AGENTS THAT INDUCE APOPTOSIS OR SENESCENCE. (5th November 2018) - Kumar, Ritesh; Lorimer, Ian
Abstract: INTRODUCTION: Glioblastoma (GBM) is the most common adult primary brain tumour. Despite maximal therapy, median survival is 14 months. Resistance to therapy in GBM is due to extensive molecular heterogeneity. Gene expression profiling demonstrates four major subtypes: proneural, neural, classical, and mesenchymal. Recently it was shown that the mesenchymal subtype of GBM cells are resistant to ionizing radiation induced apoptosis. However, the response of other subtypes to therapy with respect to apoptosis or senescence (irreversible growth arrest) remains unknown. Further investigation into the susceptibility of the molecular subtypes and mechanisms responsible for resistance may yield insight into novel therapeutic targets. METHODS: Primary Glioblastoma (PriGO) cells were harvested from 3 human patients with GBM and cultured in serum free media. Microarray analysis was used to determine the predominant molecular subtype of each cell line. Cells were then treated with radiation, chemotherapy, or serum (an agent known to induce senescence in PriGO cells). Apoptosis was measured by cell counts, caspase-3 activation, and Annexin-V positivity. Senescence was determined by SA-β-Gal assay, markers of cell cycle arrest (p21) and heterochromatin formation (PML bodies). RESULTS: PriGO8A and PriGO9A cells were predominantly classical whereas PriGO17A cells were predominantly mesenchymal. Classical PriGO8A and PriGO9A cells underwent apoptosis in response to radiation and the chemotherapeutic agent Triapine but underwent senescence in response to serum. Mesenchymal PriGO17A cells failed to undergo apoptosis or senescence in response to any agent. Inhibition of a key hyperactive pathway in mesenchymal cells, the Ras pathway, led to an increase in senescence induction. CONCLUSIONS: The molecular subtype of GBM correlates with response to therapy. The classical subtype is sensitive to agents that induce apoptosis and senescence whereas the mesenchymal subtype is resistant. Resistance to therapy may be mediated by the Ras pathway and its inhibition may render such cells susceptible to senescence inducing agents.